The Synthesis of New Comb Shaped Amphiphilic Polymers - Temürlü, Selin (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2016)
In recent years, amphiphilic polymers which consist of both hydrophilic and hydrophobic groups, have become more important in the biomedical, biochemical and pharmaceutical fields due to their ability to form supramolecular structure in the aqueous solutions. In the present thesis, four novel amphiphilic chitosan polymer including different amounts of fluorescent polyimide chromophores with comb shaped structures was successfully synthesized by polycondensation reactions. The synthesized products were analyzed using FTIR, UV-vis and Fluorescence spectrocopy. Unlike the Chitosan (CS) and Perylene-3,4,9,10- tetracarboxylic dianhydride (PDA), the new products of perylene diimide conjugated chitosan polymer are soluble in most of solvents such as DMSO, DMAc and DMF. The absorption bands were shifted bathocromically in these solvents as solvent polarity increases. The fluorescence quantum yield values of A1PCH, A2PCH, A3PCH and A4PCH were found 0.44, 0.76, 0.50 and 0.56, respectively, in DMF. Among these products, while A2PCH has the highest solubility and fluorescence properties, it has the lowest aggregation. All of PCH polymers having fluorescent properties can be used in drug delivery systems. Keywords: Amphiphilic polymers, Perylene polymers, Chitosan, Solubility

ÖZ: Son yıllarda, hidrofobik ve hidrofilik gruplardan oluşan amfifilik polimerler, sulu çözeltilerde süpramoleküler yapı oluşturma yeteneğinden dolayı biyomedikal, biyokimyasal ve eczacılık alanlarında büyük öneme sahiptir. Bu tezde, farklı miktarlarda floresans aromatik poliimit içeren 4 yeni amfifilik kitosan polimeri tarak şeklinde yapılar ile başarılı bir şekilde polikondensasyon reaksiyonu ile sentezlenmiştir. Sentezlenen ürünler FTIR, UV-vis ve floresans spektroskopi kullanılarak analiz edilmiştir. Kitosan (CS) ve perilen-3,4,9,10-tetrakarboksilik dianhidrit (PDA)’ in aksine, yeni perilendiimit konjuge kitosan polimerleri DMSO, NMP, DMAc ve DMF gibi bir çok organik çözücü içerisinde çözünmüşlerdir. Bu çözücülerde absorpsiyon bantları çözücü polariteleri arttıkça kırmızıya doğru kaymışlardır. DMF’te A1PCH, A2PCH, A3PCH ve A4PCH’ın floresans kuantum verimleri sırasıyla 0.44, 0.76, 0.50 and 0.56 bulunmuştur. Bu ürünler arasında, A2PCH en yüksek çözünürlük ve floresans özelliğine sahipken, en düşük aggregasyona sahiptir. Floresans özelliğe sahip bütün PCH polimerleri ilaç taşıma sistemlerinde kullanılabilir. Anahtar kelimeler: Amfifilik polimerler, Perilen polimerler, Kitosan ve Çözünürlük.
Master of Science in Chemistry. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Arts and Sciences, Dept. of Chemistry, 2016. Co-Supervisor: Assoc. Prof. Dr. Hamit Caner, Supervisor: Prof. Dr. Huriye İcil.
Keywords: Chemistry; Polymers-Inorganic Chemistry; Amphiphilic polymers; Perylene polymers; Chitosan; Solubility